POTENSI EKSTRAK KAYU ULIN (Eusideroxylon zwageri T et B) DALAM MENGHAMBAT PERTUMBUHAN BAKTERI Staphylococcus aureus SECARA IN VITRO - Aulia Ajizah; Thihana Thihana; Mirhanuddin Mirhanuddin (Bioscientiae, 2007)
Beside for house and heavy construction, ironwood (Eusideroxylon zwageri) has been locally used as traditional medicine against toothache. The objective of the present study was to confirm the antibacterial property of the ironwood extract against Staphylococcus aureus. Four concentrations of ironwood extract: 1%, 1.5%, 2%, and 2.5%, were applied to bacterial suspensions on nutrient broth, and  bacterial colonies were observed on MSA. Nutrient broth and Ampicillin 1% were used as negative and positive controls. The results showed that bacterial growth was retarded by 1% and 1.5% extracts, and that no bacterial growth was observed in media containing 2% and 2.5% ironwood extract as well as in positive control. The study confirmed antibacterial property of ironwood extract and concluded that the Minimal Inhibitor Concentration (MIC) of the extract was 2%.